INFLUENCE OF FINANCIAL LEVERAGE, CAPITAL INTENCITY, AND INVENTORY INTENSITY, ON TAX AGGRESSIVITY - JAENAL ABIDIN (Jurnal Ekonomi, 2023)
This study aims to determine effect of financial leverage,capital intensity,and inventory intensity on tax aggressiveness in coal mining companies on the Indonesia Stock Exchange for the 2017-2021 period. The data analysis method uses panel data regression. The results of the study show that simultaneously financial leverage,capital intensity and inventory intensity affect tax aggressiveness,this is evidenced by a probability value of 0.020531<0.05. The financial leverage variable has a negative effect on tax aggressiveness,this is evidenced by the probability value of 0.0088<0.05 and the coefficient value of -2.735938. The capital intensity variable has no effect,this is evidenced by the probability value of 0.8621>0.05. The inventory intensity variable has no effect on tax aggressiveness. This is evidenced by the probability value of 0.4244>0.05